Marion Milner e a clínica da criatividade: estilo, ética e técnica - Devito, Juliana (2015)
Aroused by the interest of studying the role of the arts in everyday life and in the therapeutic space and to deepen the study of creativity in these two fields, the objective of this research is to present the ideas and insights of the British psychoanalyst and artist Marion Milner about psychic phenomena, the therapeutic process and how they greatly expanded the scope of creativity in psychoanalysis. The study demonstrates how her work emphasizes the role of creativity and aesthetic experience in favoring the psychic growth, both the patient and the analyst, and as the psychoanalytic encounter is seen in terms of aesthetic value. The research consists of a historiographical hermeneutical study of the works of Marion Milner, through a reading that seeks to contextualize her thought on the history of psychoanalysis and a certain "school" to which she belonged in attempt to reveal the development of the of the author s thinking, since the previous moments to her psychoanalytic training until it full development. At specific times, a deconstructive reading, problematizing and interpreting is made for understanding internal strains contained in the author s thinking. The dissertation starts with a brief biography of Marion Milner and her four autobiographies, illustrating the intense research on her own subjective experience and it s influence in all the route of her career. It also presents the theory of creativity proposed by the author starting from William Blake s illustrations to the book of Job followed by the great clinical case that highlighted her as a psychoanalyst, in which is possible to follow the conditions for the emergence of creativity, also bringing a deep reflection on the fundamental problems of the constitution of the human psyche. Finally it presents the issues of ethics and psychoanalytic technique, namely the author's position regarding the analytical setting, its installation and sustain; the analytic function and possibles adjustments